CIRCUIT TRAINING GAMES TO TRAIN BASIC MOVEMENT SKILLS OF GRADE IV ELEMENTARY SCHOOL STUDENTS - Salis Hadiana Putri; Isa Ansori (STKIP Singkawang, 2025)
Lack of student participation in the implementation of essential movement learning is one of the obstacles in the process of learning basic movements. The implementation of the basic movement learning process needs to be more effective. This study aims to develop a circuit training method to train students' basic movement skills. The research method used is DBR (Design-based research). This design-based research promises to improve and contribute directly to students' abilities. The analysis is descriptive of quantitative and qualitative data obtained through observation, interviews, and direct measurements in the field. The study's results validated the feasibility of the circuit training model with each indicator of 91.67%. These results indicate that the circuit training model meets the validity and reliability requirements for testing. The results of applying the circuit training model obtained the calculation of the model's effectiveness through the statistical calculations of research data. It is known that the average value of the comparison of small-scale trials of locomotor values is 3.85, non-locomotor 3.5, and manipulative 3.42. In contrast, large-scale trials of locomotor values 3.89, non-locomotor 3.79, and manipulative 3.75 have been empirically proven that the results of the product in the form of a circle game model are very effective. The study's conclusion proves that this training circuit is effective for training basic locomotor, non-locomotor, and manipulative movement skills.